2015
DOI: 10.1111/ctr.12641
|View full text |Cite
|
Sign up to set email alerts
|

The Irish living kidney donor program – why potential donors do not proceed to live kidney donation?

Abstract: Further evaluation of the declined donor group is warranted to allow for expansion of the LD program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 17 publications
1
15
1
1
Order By: Relevance
“…The majority of the potential donors in our study were young with no significant difference in average age between accepted (29 years) and rejected (31 years) donors, which was similar to the KFSH study where the average age of potential LKDs was 32 years [10]. In contrast, the potential LKDs in our study were younger than LKDs of other studies from western countries where the average age was between 45 to 53 years [12,13]. Also, our study showed that both groups were predominantly males (79.6% vs. 86.3%).…”
Section: Discussionsupporting
confidence: 80%
“…The majority of the potential donors in our study were young with no significant difference in average age between accepted (29 years) and rejected (31 years) donors, which was similar to the KFSH study where the average age of potential LKDs was 32 years [10]. In contrast, the potential LKDs in our study were younger than LKDs of other studies from western countries where the average age was between 45 to 53 years [12,13]. Also, our study showed that both groups were predominantly males (79.6% vs. 86.3%).…”
Section: Discussionsupporting
confidence: 80%
“…Two UK single-centre cohort studies have reported the proportion of potential donors that actually go on to donate as 13% 3 and 18%. 4 Studies from the Republic of Ireland, 5 the Netherlands, 6 Poland, 7 South Africa, 8 and the USA, [9][10][11] have reported varied estimates of between 8-49% of potential donors becoming actual donors. Almost all of these studies were single-centre and the predictors of donation and of non-donation have not been well described.…”
Section: Introductionmentioning
confidence: 99%
“…These factors acted as actual controls and impacted the donation behavior. A considerable number of living donor drop-out, observed at the initial stages, could be related in part related to medical contraindications [21,22].…”
Section: Discussionmentioning
confidence: 99%